The Literacy Coach's Companion, PreK-3. - Mraz, Maryann E.; Algozzine, Bob.; Kissel, Brian T. (Thousand Oaks : Corwin Press, 2008)
This easy-to-read book contains tips, suggestions and guidance for those with responsibility for literacy in primary and early years settings.
Cover -- Contents -- Foreword -- Acknowledgments -- About the Authors -- About the Contributors -- Introduction -- Chapter 1 - Your Role and the Task at Hand: The Responsibilities of a Coach in Supporting Effective Literacy Instruction -- Chapter 2 - The Nuts and Bolts: Scheduling, Organizing, and Documenting -- Chapter 3 - The Heart of the Matter: Conferring With Teachers -- Chapter 4 - Assessment: Using Data to Inform Literacy Instruction -- Chapter 5 - Learning Communities: Supporting Collaborative Teamwork -- Chapter 6 - Ongoing Growth: Supporting Professional Development -- Appendix: For Further Reading: An Annotated Bibliography of Resources on Literacy Instruction and Coaching -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Education, Preschool; Literacy-Study and teaching; Electronic books